Ǝ-free groups as groups with the length function - Remeslennikov , V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is shown that there exists a length function with values in a finitely generated group Λ relative to which G is a Λ-free group in any finitely generated group G.